PENGEMBANGAN EVALUASI PEMBELAJARAN MATEMATIKA BERBASIS GAME MENGGUNAKAN PLATFORM WORDWALL - Sulistyorini, Yunis; Sunuyeko, Nurcholis; Rochsun; Napfiah, Siti; Mufidah, Khoirul (Universitas Insan Budi Utomo, 2023)
The development of information and communication technology is currently increasingly advanced. Information and communication are more accessible, including in the world of education. This requires educators to do more creativity by utilizing technology as a material to support the success of goals in learning. Mathematics is no exception, which is considered a complicated subject for students. Included in the learning evaluation activities of the lessons that have been given during learning activities. This research aims to create new innovations related to learning evaluation by utilizing educational games from the woodwall platform. The type of research method in this study was Research and Development using the ADDIE model which consists of five stages, namely analysis, design, development, implementation and evaluation. The validation results from media experts and material experts showed that this woodwall game media was very good for use as a learning evaluation medium. In addition to the results of the validation of the media experts and material experts, the questionnaire that was given to the respondents also showed positive results.